(untitled) (International Journal of Environmental Sciences, 2025)
Foreign direct investment (FDI) in the insurance sector encourages people to develop a habit of saving money, which in turn generates cash that can be consumed over the long term for infrastructure growth. India is without a doubt a rising economy, and many people consider it to be an appealing country to invest in, particularly in its insurance sector, which is fast expanding and undergoing tremendous change. The Indian insurance business is experiencing severe headwinds as a result of weak growth, rising prices, blocked reforms, and a worsening distribution system. This comes after a decade of great growth the industry has experienced. Foreign direct investment is a more effective alternative to reduce such issues. In light of this, the government of India has launched liberalizing measures, which include decreasing trade barriers and abolishing some prohibitions. The government has increased foreign direct investment (FDI) in the insurance sector from 26% to 49%. In terms of our Indian economy, this increase in foreign direct investment has a dual impact. The purpose of this study is to explore both the positive and negative effects that foreign direct investment (FDI) has had on the insurance industry. More capital is being brought in, new companies are entering the market, technological advancements are being made, innovative concepts are being developed, employment possibilities are being created, and the insurance business is expanding. The flow of foreign direct investment (FDI) in the insurance industry is a step that should be welcomed; however, we should also take into consideration the negative impact of FDI, which manifests itself as the repatriation of profits, which leads to a lack of social responsibility and is also detrimental to the growth of indigenous players. It is certain that the country will be exposed to risks that are not commensurate with those that an emerging market economy like ours is suited to deal with if there is an unreasonable expansion in the extent of foreign holdings in the insurance sector.